At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Solve for x: 2x - y = 3 x + y = 3?
? can someone explain this for me plz
8 Answers • Mathematics
Best Answer (Chosen by Voter)
Hi,
For this question, we are given the following system of equations:
2x - y = 3
x + y = 3
Let's make the first equation in the form of y = mx + b as shown below:
y = 2x - 3
x + y = 3
Now, substitute the first equation into the second to get:
x + 2x - 3 = 3
Combine similar terms to get:
3x = 6
x = 2
We now know that x = 2 and can plug this value into one of the given equations to get:
2 + y = 3
y = 1
FINAL ANSWER: x = 2 ; y = 1
I hope that helps you out!
[tex] \left \{ {{y=-x+3} \atop {y=2x-1}} \right. \\\\ equal\ both\ equations\\\\
-x+3=2x-1\ \ \ | subtract\ 2x\\\\
-3x+3=-1\ \ \ | subtract\ 3\\\\
-3x=-4\ \ \ | divide\ by\ -3\\\\
x=\frac{4}{3}\\\\
y=-x+3=-\frac{4}{3}+3=-1\frac{1}{3}+3=1\frac{2}{3}[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.